A review on antennas for biomedical implants used for IoT based health care. Issue 2 (19th August 2019) - Patil, Kasturi Sudam; Rufus, Elizabeth
Abstract : Purpose: The paper aims to focus on implantable antenna sensors used for biomedical applications. Communication in implantable medical devices (IMDs) is beneficial for continuous monitoring of health. The ability to communicate with exterior equipment is an important aspect of IMD. Thus, the design of an implantable antenna for integration into IMD is important. Design/methodology/approach: In this review, recent developments in IMDs, three types of antenna sensors, which are recommended by researchers for biomedical implants are considered. In this review, design requirements, different types of their antenna, parameters and characteristics in medical implants communication system (MICS) and industrial, scientific and medical (ISM) bands are summarized here. Also, overall current progress in development of implantable antenna sensor, its challenges and the importance of human body characteristics are described. Findings: This article give information about the requirements of implantable antenna sensor designs, types of antennas useful to design implantable devices and their characteristics in MICS and ISM bands. Recent advancement in implantable devices has led to an improvement in human health. Originality/value: The paper provides useful information on implantable antennas design for biomedical application. The designing of such antennas needs to meet requirements such as compact size, patients' safety, communication ability and biocompatibility.